Bumblebee Abundance in Species-Rich Grasslands in Southern Sweden Decreases with Increasing Amount of Arable Land at a Landscape Level - Per Milberg; Karl-Olof Bergman; Gabriella Fjellander; Malin Tälle; Lars Westerberg (Insects)
Conservation of bumblebee populations is essential because of their role as pollinators. Declines in bumblebee abundance have been documented in recent decades, mostly attributed to agricultural intensification, landscape simplification and loss of semi-natural grasslands. In this study, we investigated the effects of landscape composition on bumblebee abundance at different spatial scales in 476 semi-natural grassland sites in southern Sweden. The area of arable land had a negative effect on total bumblebee abundance at all scales. This was most pronounced for short-tongued bumblebees, species typical of forested landscapes, and species with medium to large colony sizes and early queen emergence. The area of semi-natural grassland had a clear negative effect up to 1 km, affecting short-tongued bumblebees in both forested and agricultural landscapes and species with medium colony sizes and early queen emergence. The negative effect of arable land on bumblebees calls for action to adapt farming practices to ensure their conservation, e.g., by reducing pesticide use, improving crop diversity and promoting the presence of floral resources and alternative bumblebee habitats, such as species-rich field margins.